Clinical significance of soft markers in second trimester ultrasonography for pregnant Korean women: a multicenter study and literature review - Hyun Sun Ko; Dong Wook Kwak; Soo-young Oh; Sae Kyung Choi; Joon Seok Hong; Han Sung Hwang; Hyun Soo Park; Hyun-Joo Seol; Moon Young Kim; Sa Jin Kim; Joong Shin Park (Korean Society of Obstetrics and Gynecology, 2022)
Objective To evaluate the clinical significance of soft markers for aneuploidy screening in Korean women. Methods We retrospectively reviewed the medical records of 5,428 singleton pregnant women who underwent sonography during the second trimester at seven institutions in South Korea. We evaluated the prevalence of the following soft markers: intracardiac echogenic focus, choroid plexus cysts, pyelectasis, echogenic bowel, and mild ventriculomegaly. We developed best-fitted regression equations for the fetal femur and humerus length using our data and defined a short femur and humerus as both long bones below the fifth centile. The results of genetic testing and postnatal outcomes were investigated in patients who had been diagnosed with aforementioned soft markers. Results The median maternal age of our study population was 33 years, and the median gestational age at the time of ultrasonographic examination was 21 weeks. We detected soft markers in 10.0% (n=540) of fetuses: 9.3% (n=504) were isolated cases and 0.7% (n=36) of cases had two or more markers. We identified only two aneuploides (trisomy 18, 46,XX,t[8;10][q22.1;p13]), of which one was clinically significant. We presented the neonatal outcomes of the fetuses with the respective soft markers. Preterm delivery, low birth weight, and small-for-gestational-age (SGA) were significantly more common in women with a shortened fetal femur (P<0.001, all). However, the presence of a shortened fetal humerus was not associated with those outcomes excluding SGA. Conclusion Soft markers in second-trimester ultrasonography have limited use in screening for fetal aneuploidy in Korean women. However, these markers can be used as a screening tool for adverse outcomes other than chromosomal abnormality.